Problematic Alcohol Use in Team and Individual Exercise Settings (Baltic Journal of Sport and Health Sciences, 2018)
Background. The scholastic literature suggests that alcohol use may be a problem in team sports, but data on the general or average exercisers are lacking. This inquiry examined the prevalence of use and the level of problematic use of alcohol in a highly heterogeneous group of team and individual exercisers. Methods. Two-hundred exercising male (n = 79) and female (n = 121) participants (M age = 26.79 ± SD = 7.88 years) answered demographic questions and completed the Alcohol Use Disorder Identifcation Test (AUDIT). Results. The rate of alcohol drinkers did not diﬀer between the groups, but males exercising in team settings reported higher levels of alcohol drinking problems than individual exercisers in general. The fndings were similar for older (aged 25 years and over) adults too, as shown by a separate analysis of the latter group. The frequency and volume of exercise were unrelated to problematic alcohol use. Cases of high level of alcohol use problems were twice as many in team than in individual exercisers. Conclusions. The prevalence of alcohol use in team and individual exercisers is similar, but problematic alcohol use is greater in the former group. Increased alcohol use problems in team exercisers seem to be limited to men and it occurs in older adults too. Men drink more than women, but the behaviour may have a general social, rather than a sport-specifc, context.Keywords: dependence, drinking, physical activity, social, substance use.